Mushroom as a potential source of prebiotics : a review. - F.M.N.A, Aida; Mustafa, Shuhaimi; Abd. Manap, Mohd. Yazid; A.G., Maaruf (Elsevier Ltd., 2009)
The demand from health conscious consumers has lead to emergence of various functional foods. Trend in food science and technology has shown development of prebiotic, which is able to modulate the human gut microbiota and improve the host health in return. The concept has been introduced for more than a decade with inulin and oligosaccharides being the most established and studied prebiotics. Better understanding on the benefits of prebiotics has urged a need for invention of new sources of prebiotics. This paper reviewed the potential of mushrooms as a source of prebiotic with thorough explanation on its concept and application.